2020
DOI: 10.1007/s00376-019-9222-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Arctic on the Predictability of Eurasian Winter Extreme Weather Events

Abstract: The linkage between the Arctic and midlatitudes has received much attention recently due to the rapidly changing climate. Many investigations have been conducted to reveal the relationship between the Arctic and Eurasian extreme events from the perspective of climatological statistics. As a prediction source for extreme events in Eurasia, Arctic conditions are crucial for extreme event predictions. Therefore, it is urgent to explore the Arctic influence on the predictability of Eurasian extreme events due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…Moreover, it has been noted that there exists considerable uncertainty in SIC data products, and the influence of this uncertainty on predictions of atmospheric circulation remains unknown (Dai & Mu, 2020). The role of SIC uncertainty in UB prediction deserves investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been noted that there exists considerable uncertainty in SIC data products, and the influence of this uncertainty on predictions of atmospheric circulation remains unknown (Dai & Mu, 2020). The role of SIC uncertainty in UB prediction deserves investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the frequency of extreme cold days during boreal winter is skillfully predicted by the ECMWF model 2–4 weeks in advance (Xiang et al., 2020). In addition to the frequency, it has also been suggested that skillful forecast of extreme cold events can be made with a lead time of more than 2 weeks (Dai & Mu, 2020). Ferranti et al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that atmospheric reanalysis data have large uncertainties in the Arctic due to the limited number of observations in the region (Inoue et al, 2011; Jung et al, 2014; Screen & Simmonds, 2011). Thus, we believe that the weather forecasts for the mid‐latitude region will improve with more accurate Arctic initial conditions, especially for extreme weather events (Dai & Mu, 2020). Ensemble atmospheric forecasts with different initial data sets revealed that additional Arctic radiosonde observations are beneficial for the forecast of persistent strong winds north of 70°N (Inoue et al, 2015).…”
Section: Introductionmentioning
confidence: 99%